2014
DOI: 10.1111/dmcn.12374
|View full text |Cite
|
Sign up to set email alerts
|

Everyday psychological functioning in children with unilateral cerebral palsy: does executive functioning play a role?

Abstract: BRIEFBehavior RESULTS Children with unilateral CP were found to have significantly decreased functioning, compared with children with typical development, on the BRIEF Behavioral Regulation Index, the BRIEF Metacognition Index, and on the SDQ emotion, conduct, hyperactivity, and peer problems subscales. Group differences were mediated by cognitive executive functioning for the BRIEF Metacognition Index (teacher and parent report), the BRIEF Behavioral Regulation Index (parent report only), the SDQ conduct subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 37 publications
1
28
0
1
Order By: Relevance
“…Studies that have focused on executive functions have reported difficulties with inhibitory control, shifting and categorization (Bottcher, 2010, Christ et al, 2003, Jenks et al, 2009, Kolk and Talvik, 2000) which can explain difficulties in everyday life (Whittingham et al, 2014). Lesions of the basal ganglia and thalamic systems may impair focused attention and executive function (Bottcher, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have focused on executive functions have reported difficulties with inhibitory control, shifting and categorization (Bottcher, 2010, Christ et al, 2003, Jenks et al, 2009, Kolk and Talvik, 2000) which can explain difficulties in everyday life (Whittingham et al, 2014). Lesions of the basal ganglia and thalamic systems may impair focused attention and executive function (Bottcher, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with able-bodied students, adolescents with PD showed no significant differences in prosocial behavior in some studies (Whittingham et al 2014;Yeates et al 2013) and lower levels of prosocial behavior in others (Brossard-Racine et al 2012).…”
Section: Peculiarities Of the Attainment Of Developmental Tasks In Admentioning
confidence: 81%
“…Studies have shown that persons with congenital disabilities such as cerebral palsy (CP) and spina bifida (SB), even if they have fairly good motor function and no intellectual disability, often have difficulties when performing everyday activities, as a result of executive dysfunction. This can involve difficulties with planning, initiation and problem solving [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%